Ekstrak Sambiloto (Andrographis paniculata) Menurunkan Jumlah Skizon, Mikrogamet, Makrogamet, dan Oosista Eimeria tenella (EXTRACT OF ANDROGRAPHIS PANICULATA DECREASED SCHIZONTS, MICROGAMETES, MACROGAMETES AND OOCYSTS NUMBER OF EIMERIA TENELLA) - CAHYANINGSIH, UMI; RIANDCI, RESSY; ISWANTINI, DYAH (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
The aim of this research was to observe the effect of ethanol extract of Andrographis paniculata givenin grading doses to the schizonts, microgamete, macrogamete, and oocytes counts of Eimeria tenella inchicken caecum. A total of ninety day old broiler chicks were used in the study. At two weeks old the broilerswere divided into six groups. Each group consisted of 15 broilers, the 6 groups were: (i) negative control(broilers did not receive any treatment); (ii) positive control (each animal were infected with 104 E. tenellaoocytes); (iii) medicine control (each animal were infected with 104 E. tenella oocytes and coccidiostat); (iv)A1 (each animal were infected with 104 E. tenella oocytes and paniculata extract 90 mg/kg body weight); (v)A2 (each animal were infected with 104 E. tenella oocytes and paniculata extract 180 mg/kg body weight);and (vi) A3 (each animal were infected with 104 E. tenella oocytes and paniculata extract 360 mg/kg bodyweight). At day 6, 9, 13, 16, and 22 post infection three broilers from each group were sacrificed and theirceca were collected for histopathological examination. The results showed that paniculata extract at dose90 mg/kg body weight and 180 mg/kg body weight was able to decrease the numbers of shizont, microgamete,macrogamete, and oocytes of E. tenella in the chicken caecum.
Keywords: Andrographis paniculata, ethanol extract, Eimeria tenella